2015
DOI: 10.1371/journal.ppat.1005220
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Regulation of Hemorrhagic Fever Virus Budding: Mechanistic Implications for Host-Oriented Therapeutic Intervention

Abstract: Hemorrhagic fever viruses, including the filoviruses (Ebola and Marburg) and arenaviruses (Lassa and Junín viruses), are serious human pathogens for which there are currently no FDA approved therapeutics or vaccines. Importantly, transmission of these viruses, and specifically late steps of budding, critically depend upon host cell machinery. Consequently, strategies which target these mechanisms represent potential targets for broad spectrum host oriented therapeutics. An important cellular signal implicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 68 publications
(59 reference statements)
1
34
0
Order By: Relevance
“…PS selective binding modules include C2 domains (49) and some PH domains (50-52 (54). In fact, VP40 was sufficient to increase cellular levels of calcium in mammalian cells (55) and its role in promoting some degree of VP40 lipid binding cannot be ruled out at this time.…”
Section: Discussionmentioning
confidence: 99%
“…PS selective binding modules include C2 domains (49) and some PH domains (50-52 (54). In fact, VP40 was sufficient to increase cellular levels of calcium in mammalian cells (55) and its role in promoting some degree of VP40 lipid binding cannot be ruled out at this time.…”
Section: Discussionmentioning
confidence: 99%
“…Among the five hit drugs, manidipine, cilnidipine, and benidipine hydrochloride were VGCC inhibitors. It has been well documented in the literature that Ca 2ϩ inhibitors serve to inhibit virus infection at the stage of either entry (15,22) or replication (18) and even at the stage of budding (23). To this end, we first reviewed all 21 calcium inhibitors included in the current library of FDA-approved drugs and found that, in addition to the four DHP VGCC inhibitors listed in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The research work done on four distinct hemorrhagic fever viruses (Ebolavirus (EBOV), Marburgvirus (MARV), Lassa Virus (LASV), and Junín Virus (JUNV)) demonstrated that EBOV, MARV VP40, and JUNV Z proteins trigger host cell Ca 2+ signals by activating the ER Ca 2+ sensing protein STIM1 and the plasma membrane ORAI1 channel. The STIM1/Orai1-mediated Ca 2+ signal is critical for EBOV and related viruses budding from host cells [35]. The suppression of STIM1 expression and genetic inactivation or the pharmacological blockade of ORAI1 inhibits infections of EBOV, MARV, and JUNV in cultured cells ( Figure 2B).…”
Section: Store-operated Calcium (Soc) Channel In Viral Assembly and Ementioning
confidence: 99%
“…It is possible that the viral proteins trigger the Ca 2+ depletion in ER or prevent ER refilled with Ca 2+ to maintain resting ER Ca 2+ levels [40][41][42]. Alternately, these viral proteins may directly modify STIM1 and uncouple the activation of STIM1 from Ca 2+ levels [35,43]. Thus, STIM1/ORAI might represent a conserved target to regulating the budding of enveloped RNA viruses and possibly DNA viruses that rely on similar host cellular proteins for budding.…”
Section: Store-operated Calcium (Soc) Channel In Viral Assembly and Ementioning
confidence: 99%